타워크레인 자율화를 위한 가상환경 플랫폼 개발에 관한 연구 - 김명준; 윤인석; 김남균; 박문서; 안창범; 정민혁; Kim, Myeongjun; Yoon, Inseok; Kim, Namkyoun; Park, Moonseo; Ahn, Changbum; Jung, Minhyuk (한국건설관리학회 논문집, 23(4), 2022)
Autonomous equipment requires a large amount of data from various environments. However, it takes a lot of time and cost for an experiment in a real construction sites, which are difficulties in data collection and processing. Therefore, this study aims to develop a virtual environment for autonomous tower cranes technology development and validation. The authors defined automation functions and operation conditions of tower cranes with three performance criteria: operational design domain, object and event detection and response, and minimum functional conditions. Afterward, this study developed a virtual environment for learning and validation for autonomous functions such as recognition, decision making, and control using the Unity game engine. Validation was conducted by construction industry experts with a fidelity which is the representative matrix for virtual environment assessment. Through the virtual environment platform developed in this study, it will be possible to reduce the cost and time for data collection and technology development. Also, it is also expected to contribute to autonomous driving for not only tower cranes but also other construction equipment. 건설현장 생산성 및 안전성 향상을 위해 건설장비 자율화를 위해 산학에서 많은 노력을 기울이고 있다. 장비 자율화를 위해서는 다양한 환경과 많은 양의 데이터 수집이 필요하다. 하지만 실제 환경에서 데이터 수집을 위한 테스트베드 확보에 많은 시간과 비용이 소모되며 불확실성 역시 크기 때문에 효과적인 데이터 수집과 처리에 어려움이 존재한다. 이에 본 연구에서는 타워크레인을 대상으로 자율화기술 개발을 위한 데이터 수집 및 테스트가 가능한 가상환경을 개발하는 것을 목표로 한다. 본 연구에서 달성한 연구성과는 다음과 같다. 1. 타워크레인 자율운행에 필요한 기술과 기술이 적용될 수 있는 환경을 운영설계 도메인, 물체 및 이벤트 감지 및 반응, 최소기능조건이라는 세 가지 성능기준을 활용하여 정의함. 2. 정의된 환경 내에서 자율화 장비의 인지, 판단, 제어를 위한 각 기술을 학습하고 테스트하기 위한 가상 환경을 Unity를 활용하여 구축함. 3. 가상환경의 목적 달성 여부를 위한 평가지표로 Visual, Motion, Functional Fidelity를 사용해 가상환경이 현실 공사현장을 충실하게 표현하고 있음을 검증함. 본 연구에서 구축한 가상환경 플랫폼을 통해 등 타워크레인 자율화에 있어 요구되는 가상 데이터를 수집하고, 각 기능들을 테스트하는 데 소모되는 비용 및 시간을 절감할 수 있을 것이며, 또한 타워크레인 뿐 아니라 타 건설장비의 자율화기술 개발에 있어서도 기여할 수 있을 것으로 기대된다.